Implementation of Legal Protection for Child Victims of Serious Abuse: Study of Decision Number 297/PID.B/2023/PN JKT.SEL - M. Arif Fazillah; Rahul Ardian Fikri; Fitria Ramadhani Siregar (CV. Era Digital Nusantara, 2026)
This study discusses the legal protection of children as victims of criminal acts of severe abuse through a case study of the Decision of the South Jakarta Regional Court No. 297/PID.B/2023/PN JKT.SìEL. Children as a vulnerable group have special rights guaranteed by national and international law. This study aims to analyze how the implementation of legal protection for child victims of severe abuse in the criminal justice process, and to assess the extent to which the judge's decision reflects the principles of justice and child protection. The method used is normative juridical with a case study approach to court decisions. The results of the analysis showthat although there are law enforcement efforts against perpetrators, protection for child victims is not yet fully optimal, especially in the aspects of psychological recovery and guarantees of non-repetition. This study recommends the need to strengthen child assistancemechanisms in legal processes and increasesynergy between child protection institutions.